Development and validation of a tool to assess self-efficacy for competence in interprofessional collaborative practice. Issue 2 (4th March 2017) - Hasnain, Memoona; Gruss, Valerie; Keehn, Mary; Peterson, Elizabeth; Valenta, Annette L.; Kottorp, Anders
ABSTRACT: Although interprofessional education and collaborative practice have gained increasing attention over the past five decades, development of rigorous tools to assess related competencies is still in infancy. The purpose of this study was to develop an instrument to evaluate health professions students' self-efficacy in interprofessional collaborative competency and to assess the instrument's psychometric properties. We developed a new instrument based on the Interprofessional Education Collaborative's (IPEC) Core Competencies for Interprofessional Collaborative Practice . In a cross-sectional study design, 660 students from 11 health programmes at an urban university in the Midwest USA completed the Interprofessional Education Collaborative Competency Self Efficacy Tool (IPECC-SET). Rasch analysis evaluated the following: (1) functioning of the instrument; (2) fit of items within each subscale to a unidimensional construct; (3) person-response validity; (4) person-separation reliability; and (5) differential item functioning in relation to gender and ethnicity. After removing seven items with suboptimal fit, each subscale demonstrated high internal validity. Two items demonstrated differential item functioning (DIF) for "Gender" and none for "Race/Ethnicity." Our findings provide early evidence of IPECC-SET as a valid measure of self-efficacy for interprofessional competence for health professions students. Additional research is warranted to establish external validity of the new instrument by conducting studies across institutions.